Sexual Health Promotion Programs in Iran and the World: A Systematic Review - Mohsenzadeh Ledari 1*, Farideh; Hosseini Tabaghdehi 2, Monirolsadat; Hajipour 3, Leila (Shahroud Journal of Medical Sciences, 2017)
Background: Lack of sexual health promotion programs in adolescents and young people is a significant public health challenge in the field of sexual health. The aim of this study was to understand sexual health promotion programs emphasizing life skills such as decision-making and self-assertiveness, with the target of enhancing sexual well-being and including studies to reduce biological adverse outcomes such as STIs or unwanted pregnancy in Iran and globally.Methods: We conducted a systematic review by searching online data bases with the keywords, sexual health; health program; and Iran, using systematic reviews such as MEDLINE and CINAHL, ISI, Scopus, Google scholar, Pubmed med, Google, Magiran, SID, Science Citation Index Expanded, Iran Medex Web of Science, ProQuest, and Springer protocols with a focus on sexual health promotion programs in Iran and in the world. Studies with the inclusion criteria and which were conducted within the past 15 years on determining and designing sexual health programs in Iran and globally were included. After extracting the articles and conferences, the specifications of documents were entered and classified in the EndNote software and duplicate cases were excluded from the study.Results: Based on the findings from the extracted studies, sexual health can be promoted through programs including sexual abstinence education and comprehensive sexual health education.Conclusions: The problem of education and of the required skills for adolescents and young adults regarding self-control and sexual health is a religious or political issue, and includes social issues which involve many different subjects; so resolving this issue requires systematic planning.